Assessing the impact of microfinance on women’s empowerment: a critical review of the literature - Shrestha, Hemanta (Innovative Research Journal, 2024)
The role of microfinance in addressing women’s dis-empowerment is the critical focus of this article. Based on secondary literature, the paper offers a critical perspective on empowerment, emphasizing the role of microeconomics activities. The issues of gender inequality and the use of microfinance as a tool to combat this inequality form the foundation of the article. This review argues that microfinance can serve as a means to emancipate marginalized sections of society, particularly women. The current state of society is bleak; however, numerous financial, microfinance, and local institutions are striving to change this reality. At present, microfinance serves as a beacon of hope in addressing various genders, class, and other social issues, especially in developing countries like Nepal.